PENGARUH INDEPENDENSI, ETIKA PROFESI, PENGALAMAN KERJA DAN TINGKAT PENDIDIKAN AUDITOR PADA KUALITAS AUDIT - Prasetyo, Eko Budi; Utama, I Made Karya (E-Jurnal Akuntansi, 2015)
Public Accountant has a crucial social role who might encounter many dilemmatic problems. In performing the professional task, a public accountant must have independency, appropriate ethic of conduct, sufficient working experience and supporting educational level.  The goal of this study is to figure out the impact of independency, ethic, working experience & level of education of auditor on the audit quality at public account office in Bali. This study used purpose sampling method. 106 questionnaires were distributed. The data obtained was analyzed by multiple regression analysis to obtain the coefficient of determinant goodness of fit. The result of this study indicate that the F and T statistical value of the independent variables, independency, ethic, working experience & level of education determine the quality of audit amongst auditors at public account offices in Bali
Keywords: Independency, Ethic, Working Experience, Educational Level, Quality of audit.